Intrinsic Electron Localization of Metastable MoS2 Boosts Electrocatalytic Nitrogen Reduction to Ammonia. Issue 32 (5th July 2021) - Lin, Gaoxin; Ju, Qiangjian; Guo, Xiaowei; Zhao, Wei; Adimi, Samira; Ye, Jinyu; Bi, Qingyuan; Wang, Jiacheng; Yang, Minghui; Huang, Fuqiang
Abstract: The advancement of efficient electrocatalysts toward the nitrogen reduction reaction (NRR) is critical in sustainable ammonia synthesis under ambient pressure and temperature. Manipulating the electronic configuration of electrocatalysts is particularly vital to form metal–nitrogen (MN) bonds during the NRR through regulating the active electronic states of sites. Here, in sharp contrast to stable 2H MoS2 without metal chains, MoMo bonding in metastable polymorphs of MoS2 bulk (zigzag chain in the 1T′ phase and diamond chain in the 1T″′ phase) is discovered to significantly increase intrinsic electron localization around the metal chains. This can enhance the charge transfer from the adsorbed nitrogen molecule to the metal chains, allowing for boosted NRR kinetics. The electrochemical experiments show that the NH3 yield rate and the faradaic efficiency of the metastable 1T″′ MoS2 rich with abundant Mo–Mo bonds are about 9 and 12 times above average than those of 2H MoS2, correspondingly. Theoretical simulations reveal the high local electron density surrounding the MoMo chains and sites can promote π back‐donation, which is beneficial for increasing nitrogen adsorption, strengthening the MN bonds, and reducing the cleavage barrier of the triple NN bond. Abstract : Metastable MoS2 with intrinsic electron localization is demonstrated as a highly efficient electrocatalyst for the nitrogen reduction reaction. The NH3 yield rate and the Faradaic efficiency of metastable 1T″′ MoS2 are about 9 and 12 times than those of 2H MoS2, correspondingly. This work develops a new class of non‐noble materials catalysts for nitrogen fixation.